2018
DOI: 10.1186/s12885-018-4314-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of methylation sites and signature genes with prognostic value for luminal breast cancer

Abstract: BackgroundRobust and precise molecular prognostic predictors for luminal breast cancer are required. This study aimed to identify key methylation sites in luminal breast cancer, as well as precise molecular tools for predicting prognosis.MethodsWe compared methylation levels of normal and luminal breast cancer samples from The Cancer Genome Atlas dataset. The relationships among differentially methylated sites, corresponding mRNA expression levels and prognosis were further analysed. Differentially expressed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 43 publications
(47 reference statements)
0
62
0
Order By: Relevance
“…ESCO2 is highly expressed in aggressive melanomas and breast cancer. 14 , 15 In gastric cancer, ESCO2 promoted cell proliferation by modulating p53 and mammalian target of rapamycin (mTOR) signaling pathways. 16 However, the biological function and clinical significance of ESCO2 in CRC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…ESCO2 is highly expressed in aggressive melanomas and breast cancer. 14 , 15 In gastric cancer, ESCO2 promoted cell proliferation by modulating p53 and mammalian target of rapamycin (mTOR) signaling pathways. 16 However, the biological function and clinical significance of ESCO2 in CRC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Being able to capture and analyze these unique invading subpopulations in the act of doing so, together with their matched non-invasive counterparts, will be key in making progress towards understanding and treating cancer. While much work has been done in this field, some of these studies compare between different patients or utilize cell lines of different invasive properties [10][11][12][13][14] , which may be confounded by existing inter-tumor heterogeneity. While there have been other reports studying spatial heterogeneity within patient samples, these studies utilized the use of formalin fixed primary tumor tissue for the identification of genomic markers 15,16 .…”
mentioning
confidence: 99%
“…Recent study demonstrated that CDCA2 promoted colorectal cancer cells proliferation by activating the AKT/CCND1 pathway in vitro and in vivo [11]. More studies were carried out to identify that CDCA could be an signature gene with prognostic value for luminal breast cancer, esophageal squamous cell carcinoma, bladder cancer, melanoma and Synovial sarcoma [12,13,21,23]. In this work, we also demonstrated that strong expression of CDCA2 in glioma was associated with advanced clinical pathologic characteristics and higher expression of CDCA2 was an an independent prognostic indicator associated with poor survival in glioma.…”
Section: Discussionmentioning
confidence: 99%